Tacit knowledge in education of a scientist (by the example of scientific psychology) - ZH. . Zagidullin (Высшее образование в России)
The article dwells upon the role of tacit knowledge in education of a scientist by the example of scientific psychology. The author leans on Mikhail Rozov’s social relays theory and formulates an idea of nonHremovability of not-verbalized components in scientific activity. Various examples of tacit knowledge manifestations are analyzed such as writing of scientific papers, operating with the referents of psychological knowledge, experimental studies, usingof collector programs. The paper substantiates the need to create conditions for young scientistsin accessing to real scientific practice and to personal contacts with the prominent scientists.